Czy Biblia mówi to, co mówi? Feministyczna interpretacja tekstu biblijnego Elisabeth Schüssler Fiorenzy - Gomola, Aleksander (Er(r)go. Teoria - Literatura - Kultura, 2007)
Aleksander Gomola Does the Bible Say What It Says? A Feminist Interpretation of the Biblical Text by Elisabeth Schiissler Fiorenza. The interpretation of the Bible postulated by feminist theology constitutes an interesting social and religious phenomenon, as it locates itself at the intersection of the social and religious discourses, thereby drawing its inspiration from both, and advocating new solutions concerning faith and social life. This essay discusses "the transformative dance of interpretation" of the Bible: a hermeneutic strategy which has been developed by the feminist theologian E. S. Fiorenza. The strategy's aim has been to recover for women their rightful place within the community of the faithful and to revise the male-centered mode of representing the history of Christianity. That is achieved by a critical analysis of the biblical text, with particular attention paid to its patriarchal slant, the rejection of those elements which depreciate women and a creative reinterpretation premised on the assumption of the existence of the original christianity of the "discipleship of the equal", that is a community where men and women enjoyed equal rights. The above mentioned strategy, in contrast with traditional methods of interpretation, bestows upon the reader a superior role in relation to the text, which constitutes a major departure from the tradition of biblical interpretation.